A tale of magic... - Colfer, Chris, 1990- (Little, Brown and Company, 2019)
Fourteen-year-old Brystal Evergreen risks everything by opposing her kingdom's repression of women, but Madame Weatherberry, seeing her potential, invites her to a school where she hopes to change the world's perception of magic.